GROUP GRID AND ROUNDTABLE FOR TEACHING WRITING OF DESCRIPTIVE TEXT - Urunami, Silvia; Bharati, Dwi Anggani Linggar; Faridi, Abdurrachman (ELT Forum: Journal of English Language Teaching, 2017)
This paper is based on a research aiming to describe the effectiveness of Group Grid and Round Table technique in teaching writing descriptive text. By using a quasi-experimental design, the research involves the tenth grade students of SMA Taruna Nusantara Magelang in the academic year of 2016/2017. In this case, the experimental group is X IA 12 and the control group is X IA 10. The result shows that the mean score of the experimental group increases from 69.15 to 79.34 after several treatments applying the strategy. The t-test computation reveals that there is a significant difference between the two groups. It is proven by the tvalue (2.844) which is higher than the ttable (1.998). In addition, a questionnaire is administered to know the effect of implementing the technique to the students. The analysis shows that 59.37% of the students agree that the implementation of the strategy assists their comprehension and 31.25% of them even strongly agree towards the statement. Therefore, Group Grid and Round Table technique is proven an effective strategy in teaching writing descriptive text.